"Whisking of ugly tissue"... A surgical management of gingival fibromatosis in a 15-year-old girl: A rare case report - Srinivasa Tenkasale Siddeshappa; Sushmita Deonani; Sonika Nagdeve; Ramreddy Krishnarao Yeltiwar (Wolters Kluwer Medknow Publications, 2015)
Gingival fibromatosis is a condition characterized by a slow, progressive increase in the gingival tissue that develops as either an isolated disorder or as part of the clinical characteristics of diverse syndrome. The present case report describes a rare case of gingival fibromatosis and its management using scalpel in combination with electrosurgery. A 15-year-old girl patient presented with a chief complaint of gingival overgrowth covering all the surfaces upper and lower teeth. The growth was excised with periodontal knife in combination with electrosurgery under local anesthesia. After 1-year of follow-up, healing was uneventful with no recurrence. Combined technique for the removal of gingival overgrowth represents a unique treatment approach where minimal postoperative bleeding and discomfort were observed.